Determination of olanzapine for therapeutic drug monitoring in schizophrenia patients by LC/MS method. (7th January 2019) - Albayrak, Mevlut; Kadioglu, Yucel; Yaman, Mehmet Emrah; Senol, Onur; Oral, Elif
Abstract: Olanzapine is an atypical antipsychotic drug from the thienobenzodiazepine family which displays efficacy in patients with schizophrenia and related psychoses. A novel LC/MS method was developed and validated for determination of olanzapine in schizophrenia patients' plasma. A liquid–liquid extraction procedure was carried out using 5 mL diethyl ether–diisopropyl ether mixture (1:1, v/v). Average recovery of the extraction procedure was 94.8%. Chromatographic separation was performed on reversed‐phase C18 column (250 × 2.0 mm, 5 μm) using mixture of deionized water (trifluoro acetic acid 0.1%)–acetonitrile (20:80, v/v) as mobile phase at a flow rate of 1 mL/min. Irbesartan was used as internal standart and total run time was 2.5 min. Mass spectrometric analysis were carried out in selective‐ion montoring mode, and detected olanzapine at m / z 313.1 and IS at m / z 429.4 in all forms of the ions. The calibration curve of olanzapine was linear in the range 2–300 ng/mL ( r 2  > 0.9993). The interday and intraday precisions (RSD) were <7.55%, and accuracy was >7.59% ( n  = 6). The proposed study was successfully validated with respect to the US Food and Drug Administration guidelines.